2002
DOI: 10.1088/0953-8984/14/26/312
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic relaxation phenomena in the superspin-glass system [Co80Fe20/Al2O3]10

Abstract: Relaxation and temperature cycles of thermoremanent magnetization, M TRM , in the superspin-glass phase of [Co 80 Fe 20 (0.9 nm)/Al 2 O 3 (3 nm)] 10 have been investigated. The relaxation of M TRM exhibits ageing phenomena. In negative temperature cycles for temperature steps larger than 1 K the magnetic state is retrieved (memory effect) on returning to the measurement temperature. This property is independent of the application of a fi eld step during intermediate cooling. In positive temperature cycles the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…From the viewpoint of 1), we consider that the permalloy nanoparticle system studied by Sun et al is closer to a superparamagnet, while the Fe-N system studied in the present work and the Co-Fe nanoparticle system studied by Sahoo et al 30,31,37 are closer to a superspin glass. Lastly, we have argued that these two aspects peculiar to superspin glasses are qualitatively reproduced by the random energy model, and are well interpreted by the droplet theory in the field of the spin-glass study.…”
Section: Discussionmentioning
confidence: 64%
“…From the viewpoint of 1), we consider that the permalloy nanoparticle system studied by Sun et al is closer to a superparamagnet, while the Fe-N system studied in the present work and the Co-Fe nanoparticle system studied by Sahoo et al 30,31,37 are closer to a superspin glass. Lastly, we have argued that these two aspects peculiar to superspin glasses are qualitatively reproduced by the random energy model, and are well interpreted by the droplet theory in the field of the spin-glass study.…”
Section: Discussionmentioning
confidence: 64%
“…1b), with peaks appearing at times close to the corresponding wait times similarly as observed in atomic spin glasses [8]. We have previously shown that the relaxation of thermoremanent magnetization exhibits similar aging phenomena albeit showing less clear correlations between t w and tðS max Þ [9]. Presumably this was due to non-linearity effects owing to comparatively large field steps applied.…”
mentioning
confidence: 63%
“…Also, the magnetization of the FC curve keeps increasing beyond the maximum of the ZFC curve. Thus, we may identify the temperature at which the maximum of the ZFC curve occurs as a superparamagnetic blocking temperature, T B , rather than a spin-glass-like freezing temperature [9]. To further confirm the absence of spin-glass-like aging phenomena, ZFC/FC data were also collected on a sample of dense (40 mg Fe 2 O 3 /ml) frozen ferrofluid, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%